Determination of oxygen permeability in soft contact lenses using a polarographic method : estimation of relevant physiological parameters - González-Méijome, José Manuel (2008)
This work reports the apparent oxygen transmissibility Dk/t)app of four silicone hydrogel (Si-Hy) contact lenses (CLs). A method is described that allows the estimation of the oxygen tension at the lens-cornea interface for closed- and open-eyelids situations combining the instrument oxygen transmissibility (IOT) and corneal parameters such as corneal thickness, corneal permeability, and oxygen flux across the cornea. From these results, the biological oxygen apparent transmissibility (BOAT), equivalent oxygen percentage (EOP), partial pressure, (ptc), of oxygen at the cornea-CL interface and oxygen flux, (jc), were also obtained. This method allows the evaluation of the physiological environment under the lens using the formulations described in previous studies. The oxygen performance of four Si-Hy materials was evaluated using a polarographic cell coupled to a permeometer. Measurements of the apparent transmissibility, (Dk/t)app, and permeability, Dk, were performed in stacks containing from 1 to n repeated lenses and, from the values obtained, the error involved in the measurements in single samples was estimated. It was found that the values of (Dk/t)app and Dk obtained following the two different procedures (stack method and measurement of single sample) were significantly different from the nominal values given by the manufacturer, particularly for some samples. However, the impact of these differences on the values of the other physiologically relevant parameters (BOAT, EOP, ptc, and jc) was not significant. Furthermore, these parameters were similarfor the four lenses in spite of the different (Dk/t)app measured. The relationships of (Dk/t)app with theremaining physiological parameters were calculated and graphically represented for open and closed-eyelid conditions.